Musa conservation & documentation: Proceedings of a workshop, 11-14 December 1989, Leuven, Belgium - International Network for the Improvement of Banana and Plantain (1990)
This workshop, organized jointly by INIBAP and IBPGR, aimed to lay the foundation for international coordination in the conservation of banana and plantain germplasm and for the use of an international 'language' in the collection and exchange of relevant data. These proceedings comprise the following: (1) workshop background paper; (2) general recommendations of both the conservation and documentation working groups; (3) 14 papers on various aspects of Musa genetic resources work; and (4) lists of Musa germplasm collections in Latin America and the Caribbean, Central and West Africa, East Africa, Southeast Asia and the Pacific and at the INIBAP Transit Center, Leuven, Belgium. (Abstract © CAB ABSTRACTS, CAB International)